ANALYSIS OF THE STRUCTURE OF THE INVESTMENT PORTFOLIO OF PRIVATE PENSION FUNDS IN ROMANIA - OANA DOBRE-BARON (Annals of the University of Petrosani: Economics, 2017)
The practice of many European countries, Romania becoming a member of the European Union, as well as the conclusions of several studies undertaken by international organisations which show a decrease and aging of our nation’s population, have caused the authorities to rethink the public pension system, redirecting part of the contributions paid by romanians to this system towards a private one. A portfolio of private pension funds has been created, namely Pylon II. The following study seeks to present the principles behind the functioning of Pylon II, as well as to make an analysis of the main indicators that characterise this sistem, especially the structure of the investment portfolios of the seven privately managed pension funds from Romania between 2012 and 2016.